2018
DOI: 10.1017/s0956536118000135
|View full text |Cite
|
Sign up to set email alerts
|

The Early Izapa Kingdom: Recent Excavations, New Dating and Middle Formative Ceramic Analyses

Abstract: Izapa is famous for its monumental architecture and extensive corpus of carved stelae dated to the Late Formative Guillén phase (300–100 calb.c.). The site was first established, however, as the capital of a kingdom during the second half of the Middle Formative period (750–300 calb.c.). Little is known of the first centuries of the site's occupation or how this early kingdom coalesced with Izapa as its capital. In 2012, the Izapa Regional Settlement Project (IRSP) excavated 21 test units and ran 10 radiocarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…The mud deposit of the San Antonio lahar, which occurred between 30 b.c.-a.d. 80 during the Hato phase, is located somewhere between these Middle and Terminal Formative layers. We suggest that the grey layers documented by Rosenswig et al (2018) in Mound 30 may be volcanic material related to the flood event. A careful analysis of this material may be needed.…”
Section: Interpretation Of the Simulations And Related Hazardsmentioning
confidence: 79%
See 2 more Smart Citations
“…The mud deposit of the San Antonio lahar, which occurred between 30 b.c.-a.d. 80 during the Hato phase, is located somewhere between these Middle and Terminal Formative layers. We suggest that the grey layers documented by Rosenswig et al (2018) in Mound 30 may be volcanic material related to the flood event. A careful analysis of this material may be needed.…”
Section: Interpretation Of the Simulations And Related Hazardsmentioning
confidence: 79%
“…Lowe et al (1982) concluded that, during the Hato phase, Izapa halted its constructional growth and that this cessation of construction activity in the ceremonial center coincided with its partial abandonment. As Rosenswig et al (2018) clarify, however, certain limited yet impressive modifications to the ceremonial center, especially to the northern side of the Mound 30 platform, continued during the Terminal Formative period Itstapa phase (Figure 2a). These alterations of the Middle and Late Formative center were linked to a refocusing of construction activity to the Group F area north of the ceremonial center (Rosenswig and Mendelsohn 2016).…”
Section: Interpretation Of the Simulations And Related Hazardsmentioning
confidence: 88%
See 1 more Smart Citation
“…and a.d. 400, concentrated on the centuries following Izapa's Formative-period apogee and the disruption caused by the Tacaná eruption. In her contribution to this Special Issue, Mendelsohn (2018) presents excavation data from the area south of lower Izapa and questions Lowe et al's (1982:139, 194) hypothesis that the Hato phase witnessed an intrusion by an outside ethnic group. She proposes, instead, that increased participation in trade networks for elite goods and a transformation in the institution of kingship at Table 1), which is consistent with the Hato phase lasting from 100 b.c.…”
Section: Introducing Izapa 257mentioning
confidence: 87%
“…Sediment core data presented by Neff et al (2018) also indicate that mangrove wood was being burned for fuel during the Bermudez complex. Occupation in the estuary then decreased significantly during the Terminal Formative Soledad phase (a.d. 0-250), when Izapa was experiencing volcano-induced political problems (Macias et al 2018;Mendelsohn 2018).…”
Section: Regional Patterns Of the Formative-period Izapa Kingdommentioning
confidence: 99%